1999
DOI: 10.1046/j.1365-2583.1999.00134.x
|View full text |Cite
|
Sign up to set email alerts
|

Intragenomic heterogeneity of a ribosomal DNA spacer (ITS2) varies regionally in the neotropical malaria vector Anopheles nuneztovari (Diptera: Culicidae)

Abstract: We investigated intragenomic heterogeneity of ITS2 within twenty individual Anopheles nuneztovari (subgenus Nyssorhynchus) from five geographical localities in the neotropics (three from Brazil and one each from Colombia and Venezuela) by cloning and sequencing PCR-amplified copies of this spacer. Intragenomic heterogeneity was observed in thirteen of twenty mosquitoes of both sexes from all localities. As estimated by uncorrected P, however, mean sequence divergence was greater in mosquitoes from Brazil (PR =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
42
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(47 citation statements)
references
References 34 publications
4
42
0
1
Order By: Relevance
“…[61][62][63] The samples from the Amazon Basin tended to have higher genetic diversity, in particular nucleotide diversity, than those from Bolivia/ Colombia/Venezuela. These differences were congruent with those of previous mitochondrial and nuclear gene studies 22,[25][26][27][28]64 and can be indicative of cryptic species, or possibly differences in effective population size ( N e) or other events related to the history of these populations. The highest genetic diversity was observed for localities in the central region of Amazonian Brazil.…”
Section: Discussionsupporting
confidence: 88%
“…[61][62][63] The samples from the Amazon Basin tended to have higher genetic diversity, in particular nucleotide diversity, than those from Bolivia/ Colombia/Venezuela. These differences were congruent with those of previous mitochondrial and nuclear gene studies 22,[25][26][27][28]64 and can be indicative of cryptic species, or possibly differences in effective population size ( N e) or other events related to the history of these populations. The highest genetic diversity was observed for localities in the central region of Amazonian Brazil.…”
Section: Discussionsupporting
confidence: 88%
“…nuneztovari A. Additionally, several clones showed a polymorphic A insertion after the G > T transversion in specimens with 3 GAs. The A insertion was absent in specimens from Suriname and Brazil published by Fritz et al (1994), but was observed by Onyabe and Conn (1999) in other Brazilian populations. These authors also showed that T (transversion) + A (insertion) is more frequent in specimens from states of Pará and Amazonas than in those from state of Rondônia (Brazil).…”
Section: Discussionmentioning
confidence: 65%
“…Ribosomal DNA is known to exhibit intra-individual variations in rDNA for species within the genus Anopheles (Onyabe and Conn, 1999;Beebe et al, 2001;Whang et al, 2002), and is currently used to differentiate species based on fixed, interspecific mutations (Collins and Paskewitz, 1996). Malaysian Borneo populations of the A. sundaicus complex exhibited a fixed deletion in position 532 of the ITS2 sequence.…”
Section: Mtdna Versus Its2mentioning
confidence: 99%